Efecto repelente de una loción elaborada a base de extractos fluidos de hojas de Azadirachta indica y Eucalyptus globulus - Vilchez Castillo, Antonio (2017)
In this research, we determined the pharmacognostic study of leaves of Azadirachta indica and Eucalyptus globulus, as well as the repellent effect of a lotion based on fluid extracts of leaves of these two plants, thus reporting parameters of shape, surface, consistency and Dimensions of the leaves, organoleptic characteristics like scent suigéneris, dark green color, bitter taste, whole fracture, fresh condition. The physical-chemical parameters, for Azadirachta indica, residual moisture 2.43 g, solubles soluble in ethanol of 70º GL 0.77 g, total ashes 1.84 g, and ash insoluble in acid 33,13 g, in its phytochemical screening Was found resins, lactones, triterpenoids, phenolic compounds, quinones and tannins, for Eucalyptus globulus, physicochemical parameters, residual moisture 3.07 g, solubles soluble in ethanol of 70º GL 0.714 g, Total ash 1.90 g, and ash insoluble in acid 27.16 g, in its phytochemical screening were coumarins, reducing sugars, lactones, phenol compounds, quinones, flavonoids and tannins, the basal was compared with the bites to different Times after application of the lotion, a statistically significant difference was found, which indicates that there is repellent effect of the lotion and that it is stable at 1 h, 2 h, 3 h, 4 h, and 5 h, It was determined the repellent effect of this lotion elaborated with fluid extracts of leaves of Azadirachta indica and Eucalyptus globulus, against the stings of Aedes aegypti mosquitoes.